2013
DOI: 10.1136/bcr-2013-200387
|View full text |Cite
|
Sign up to set email alerts
|

Disassociation at the head–trunnion interface: an unseen complication of modular hip hemiarthroplasty

Abstract: A woman in her mid-90s underwent a left uncemented bipolar hemiarthroplasty for an intracapsular femoral neck fracture. Postoperative radiographs at 48h showed a disassociation of the left femoral prosthesis at the head–trunnion interface, with the bipolar head remaining in the acetabulum. There was no preceding trauma and the patient had mobilised postoperatively. The hip was revised to a monopolar head, and the patient's hip was protected postoperatively in a brace limiting flexion and external rotation. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Dissociation is rare and has been reported in only a few case reports [4,7,8,13,16]. The reasons for disassociation after hemiarthroplasty have been reported as component selection and alignment, surgical technique, and patient factors [4,7,8,11,13,15,16]. Varley and Parker [25] reported that dissociations accounted for 12% of all dislocations in bipolar prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation is rare and has been reported in only a few case reports [4,7,8,13,16]. The reasons for disassociation after hemiarthroplasty have been reported as component selection and alignment, surgical technique, and patient factors [4,7,8,11,13,15,16]. Varley and Parker [25] reported that dissociations accounted for 12% of all dislocations in bipolar prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…GTF as a cause of dissociation at the femoral head-trunnion interface has just recently been studied, and over the past decade, there appears to be an increase in reported cases [3] . Dissociation at the femoral head-trunnion interface is more commonly seen following a traumatic event, such as reduction of a hip dislocation in which the inferior edge of the head is distracted against the acetabular component causing dissociation of the 2 components, or after direct trauma to the hip [10] . This case report demonstrates GTF with malformation of the trunnion leading to dissociation at the head-trunnion interface.…”
Section: Discussionmentioning
confidence: 99%
“… 26 There are very few case reports available in the literature about the dissociation of bipolar cups. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 19 , 20 , 21 The dissociation between the components may occur during the hip dislocation, the reduction maneuvers, or spontaneously without any dislocation. 8 , 10 Three types of dissociation are described.…”
Section: Discussionmentioning
confidence: 99%